Contributing Factors of Personal Protection Equipment (PPE) Utilization among Sand and Gravel (SSG) Mine Workers - Tristiana, Rr Dian; Pravitasari, Ratih; Wahyuni, Erna Dwi (International Journal of Psychosocial Rehabilitation, 2020)
The low utilization of personal protection equipment (PPE) can cause a high rate of work accidents. The contributing factors related to PPE utilization need to be explored. This study aimed to explore the contributing factors of personal protection equipment utilization among sand and gravel mine workers. This study was cross-sectional. A total of 118 respondents participated in this study. The independent variables were belief, knowledge and the attitude of the sand and gravel miners, the availability of PPE and employee attitude. The dependent variable was the sand workers’ behavior in using the PPE. The data were collected using a questionnaire, and tested using Spearman Rho test with a significance level of p